Obtaining dry protein concentrates from secondary gelatin products - R. A. Voroshilin; A. Yu. Prosekov; M. G. Kurbanova (Новые технологии)
The article presents the investigation of the chemical composition of a collagen-containing broth obtained during gelatin production at the stage of defatting bony raw material. Collagen broth is a minor by-product from gelatin production. The aim of the research is to analyze the effect of the duration of the hydrothermal treatment of collagen raw materials on the concentration of high-protein broths by using spray drying. To carry out a set of experimental studies they used broth obtained by the method of hydrothermal treatment of bone at a temperature of 95±5°C for 90 to 180 minutes and its dry concentrate obtained later at the Mini Spray Dryer B-290 laboratory spray drying model (Buchi, Sweden). According to the research results, it has been revealed that the duration of the hydrothermal treatment affects the indicators of fat, protein, and dry matter content in broths. When being treated for 90 minutes, the dry matter content is in the range of 8,1 %, which is 46 % less than with a treatment time of 180 minutes. When the duration of the hydrothermal treatment of raw materials increases, the gelation time of the obtained broths reduces at temperature conditions of 4±2°C. After the spray drying process physicochemical parameters of the obtained dry collagen concentrates have been determined. In the dry concentrate the dependence of the indicator of the content of the mass fraction of protein on the duration of the hydrothermal treatment of broths is observed, the values range from 64,19 % to 82,89 %. The gelling capacity of all samples is high. The obtained dry concentrates are in the form of white to light cream color homogeneous powder.